EFFECT OF LIQUID ORGANIC FERTILIZER OF RABBIT URINE ON THE GROWTH AND YIELD OF TWO SPINACH VARIETIES (Amaranthus sp.) - alwan alwan; Istirochah Pujiwati; Anis Sholihah (AGRONISMA, 2022)
Spinach (Amaranthus sp) is a vegetable plant that is favored by all levels of society in Indonesia. Spinach provides health benefits such as a cold feeling in the stomach, facilitates digestion, and contains many nutrients, including protein, minerals, calcium, iron, vitamins A and C. In addition, spinach also contains many mineral salts including calcium, phosphorus , iron to promote growth and maintain health. The research was carried out for Â± 2 months, starting from May to July 2020. The research was conducted on the land of the Bumi Asri Sengkaling residential farmer, Mulyoagung village, Dau sub-district, Malang district. With an altitude of 633 meters above sea level. This study was conducted using a factorial randomized block design, the first factor: rabbit urine LOF concentration consisting of 4 levels, namely: U0 = without rabbit urine LOF, U1 = 50 ml/L rabbit urine LOF, U2 = 100 ml/L rabbit urine LOF, U3 = 150 ml/L LOF rabbit urine. The second factor is the variety of spinach seeds used, consisting of 2 levels, namely: V1 = Green spinach varieties, V2 = Red spinach varieties. From the two factors obtained 8 combinations of each treatment was repeated 3 times using 10 samples for each treatment. The results showed that there was an interaction between the concentration of rabbit urine and two varieties of spinach on plant height at 15 DAP, stem diameter at 11 and 15 DAP and number of leaves at 27 DAP. The green spinach variety gave the best growth response at a urine concentration of 50 ml/L on the plant height variable and a concentration of 150 ml/L on the stem diameter variable, while red spinach without urine showed the best growth on the variable number of leaves and a concentration of 150 ml/L on the variable. total root length. The best growth of spinach plants was at a concentration of LOF rabbit urine 50 ml/L for plant height, 100 mL/L in stem diameter. The growth of green spinach variety was better than red spinach in terms of plant height, number of leaves, meanwhile the fresh weight of red spinach variety was higher at 25.71 t/ha than green spinach 20.51 t/ha.